Outlining the thermal posdepositional evolution of the Ordovician successions of northwestern Argentina by clay mineral analysis, chlorite geothermometry and Kübler index - Do Campo, Margarita Diana (2017)
The thermal post-depositional evolution of metapelitic and metavolcanic rocks of the upper CambrianOrdovician succession in the Central Andes of northwestern Argentina, was estimated through X ray diffraction of clay mineral analysis, Kübler Index (KI), SEM-EDS study of selected samples and chlorite geothermometry. The study area comprise five representative regions in Puna and Cordillera Oriental, namely at Sierra de Santa Victoria (Nazareno and Santa Victoria river areas), Cordón de los Siete Hermanos (Yavi), Sierra de Rinconada and Sierra de CochinocaEscaya. The paleotemperatures obtained with the chlorite geothermometer, in coincidence with KI values, show an E-W trend from diagenesis/low anchizone in the eastern flank of Sierra de Santa Victoria, to high anchizone/epizone in the Puna, with intermediate values in the western flank of Sierra de Santa Victoria. This trend, in conjunction with the development of slaty cleavage in the Ordovician rocks from Yavi, Sierra de Cochinoca-Escaya and western localities coincide with the limits proposed for the “Ocloyic deformation belt”. The common occurrence of kaolinite in the slates and the metavolcanic rocks of Sierra de Cochinoca-Escaya, coupled with the substitution of chlorite by interstratified lower-temperature phases in most of these rocks and the occurrence of jarosite in a metadacite, indicate presence of hydrothermal fluids with high H+ /cations ratios, producing acid type alteration (Utada, 1980), at temperatures between 100 and ~300 °C. The hydrothermal alteration should have been subsequent to the maximum burial and the attainment of epizonal metamorphism, and was very probably related with the posthumous activity of the Ordovician volcanic arc. The widespread occurrence of retrograde diagenesis products (smectite, kaolinite, as well as interstratified Chl/Sm and Chl/Vrm phases) in the anchizonal/epizonal metapelites of Sierra de Cochinoca-Escaya and Sierra de Rinconada constitute, up to our knowledge, the first report of an extensive hydrothermal activity affecting not only the metavolcanic rocks but also the Lower Ordovician sediments of northern Puna.